ANALISIS PERSPEKTIF GURU KABUPATEN PROBOLINGGO TERHADAP MUNCULNYA KEBIJAKAN REKRUTMEN GURU MELALUI MARKETPLACE - Winarsih, Nining; Silviyana, Silviyana; Hakim, Faisol (Citra Media Publishing, 2024)
A teacher is someone who imparts knowledge to the students he teaches. In selecting quality teachers, schools usually recruit teachers using various criteria and methods. However, what has been voiced recently is regarding the teacher recruitment policy through the marketplace. The aim of this research is to analyze the perspective of Probolinggo Regency teachers regarding the emergence of teacher recruitment policies through the marketplace. The method used in the research is a qualitative method. The research objects are all teachers in Probolinggo Regency. Data collection techniques are interviews, questionnaires and documentation. Data analysis techniques, data reduction, data presentation and drawing conclusions. The results obtained were those who agreed and disagreed with teacher recruitment through the marketplace. The reason they disagree is because they feel they don't honor and respect teachers, while those who agree are because it makes it easier for school principals to find the teachers they need. This research can be used as a reference for the government in determining teacher recruitment policies through the marketplace which will be realized in 2024.